Spatial Variation in Food selection, Feeding Habits, and Ontogenetic Diet Shift of Labeobarbus altianalis (Boulenger, 1900) along River Nyando, Kenya - Chemoiwa , Emily Jepyegon; Hilda , Hilda (African Journal of Education,Science and Technology (AJEST), 2018)
The food and feeding habits of Labeobarbus altianalis (Boulenger, 1900) was studied based on 170 gut samples collected along River Nyando, Kenya. This study was aimed at determining the spatial variation in feed and feeding habits of L. altianalis. Three sites S1 at upper region; S2 at mid region and S3 at lower region closer to the river mouth were sampled. Fish sampling was done using an electrofisher and identified in the field. The length and weight of L. altianalis were taken in the field to the nearest 0.1 g. The stomachs were gutted and then preserved in vials in 5% formalin for later examination of dietary components. Ten dietary groups were identified from the guts. There were significant variations in the proportion of the plant materials among the three sampling sites (Chi-square; χ2 = 129.12, df = 20, P <0.0001). At S1, ephemeroptera, cladocera and detritus were the dominant food items because of their availability in the environment and a higher proportion of mature fish, while at S2 food materials were dominated exclusively by insects and diptera and at S3, plant materials, insects and diptera were more dominant. Gastropods plant seeds and algae were consumed by the fish but at low abundance at all the sampling sites due to lack of preference by the fish. At sampling sites there were strong negative electivity for rotifers and copepods by the fish. At S1, coleoptera and insects were positively selected while at site S2, there was negative electivity for plant materials, invertebrate taxa and gastropods. At S3, strong negative electivity was observed for algae, gastropod shells and cladocera with plant materials, coleopteran and detritus having positive selection.